Outcome of Otologic Symptoms after Temporomandibular Joint Arthrocentesis. Issue 4 (June 2015) - Tozoglu, S.; Bayramoglu, Z.; Ozkan, O.
<x xml:space="preserve">Abstract</x> Abstract The objectives of this study were to determine the prevalence of otologic complaints in patients with temporomandibular joint (TMJ) closed lock (CL), and to evaluate the efficacy of arthrocentesis in temporomandibular disorder (TMD) patients with otologic symptoms. Fifty-seven patients with TMJ CL were included in this study. The pre-treatment evaluations included assessment of the maximum mouth opening (MMO); pain level in palpation of the affected TMJ; pain level with function; and otologic complaints, including otalgia, tinnitus, vertigo, and hearing loss. Arthrocentesis treatment was performed for all the patients, and post-treatment data were recorded 1 month later. Before arthrocentesis and lavage, the mean MMO was 24.67 ± 4.61 mm; the mean tenderness score was 7.02 ± 1.09; and the mean score for pain in function was 6.86 ± 1.31. Following TMJ arthrocentesis and lavage, the mean MMO was 39.81 mm ± 4.56 mm; the mean tenderness score was 2.37 ± 0.65; and the mean score for pain in function was 2.45 ± 0.69. Seventeen (29.82%) patients reported at least 1 otologic complaint, 17 (29.82%) patients reported otalgia, and 8 (14.04%) patients reported tinnitus. Vertigo was noted in 5 (8.77%) patients. Complaints of hearing loss were not noted in any of the patients. After treatment, 14 patients no longer complained of otalgia, 5 patients no longer complained of tinnitus, and 2 patients no longer complained of vertigo. This represented a significant improvement in the patients' condition, especially in patients with otalgia (P < 0.0006). As evident from the results of this study, arthrocentesis procedures reduce both TMD symptoms and otologic complaints.